DETERMINATION OF URINARY SYSTEM INFECTIONS RISK FACTORS AFTER KIDNEY TRANSPLANTATION: RETROSPECTIVE ANALYSIS: BÖBREK NAKLİ SONRASI ÜRİNER SİSTEM ENFEKSİYONLARI RİSK FAKTÖRLERİNİN BELİRLENMESİ: RETROSPEKTİF ANALİZ - SOYLU, Dilek; SOYLU, Ayşe (Göbeklitepe Medical Science Journal, 2025)
This study was conducted to determine the risk factors of urinary tract infection after kidney transplantation. It was designed as a retrospective and descriptive study. The study was completed with data from 99 patients. Age, gender, year of transplantation, chronic diseases, transplant type, graft loss, length of hospital stay, laboratory results, dialysis duration, DJ (double J ) catheter duration, antibiotic use, steroid and immunosuppressive drug doses were investigated in patient files and hospital information system records. 48.5% of the patients were hospitalised for 19 days or longer, 47.5% used more than 6 mg prednisone, 98.0% used double immunosuppressants and 19.2% had an additional surgical procedure. The duration of DJ catheter stay was 44.22±26.46 days. Postoperative urine culture produced infection on the 7th day in 4%, 14th day in 6.1%, 1st month in 11.1%, 3rd month in 12.1% and 6th month in 11.1%. CRP levels were found to be ≥5mg/l in 47.5% of the patients on postoperative day 1, 68.7% on postoperative day 3 and 51.5% on postoperative day 7. Procalcitonin levels were found to be ≥0.25 ng/mL in 27.3% of the patients on postoperative day 1, 31.3% on postoperative day 3, and 37.4% on postoperative day 7. Age, gender, chronic diseases, duration of DJ catheter, duration of dialysis, duration of hospital stay and number of immunosuppressive drugs used are among the risk factors for the development of UTI.